Leptin and its Receptors in Human Placenta of Small, Adequate, and Large for Gestational Age Newborns - Lazo-de-la-Vega-Monroy, Maria-Luisa; González-Domínguez, Martha I.; Zaina, Silvio; Sabanero, Myrna; Daza-Benítez, Leonel; Malacara, Juan Manuel; Barbosa-Sabanero, Gloria (Hormone and Metabolic Research, 2017)
Alterations in birth weight impact postnatal outcome and adult metabolic health. Therefore, fetal growth regulation is crucial for preventing chronic metabolic diseases. Leptin has been suggested to play an important role in placental and fetal growth, albeit its specific mechanisms of action have not been elucidated. The aim of this study was to analyze leptin concentrations in placenta, cord blood, and maternal blood of SGA, AGA, and LGA (small, adequate and large for gestational age, respectively) newborns, as well as placental leptin receptor (LEPRa and LEPRb) protein expression. We performed a cross-sectional comparative study in 3 groups of healthy mothers and their term newborns at delivery (SGA, AGA, and LGA, n=20 per group). Placental, maternal blood, and cord blood leptin content were measured by ELISA. Placental LEPRa and LEPRb protein expression were determined by Western Blot. Maternal leptin concentrations correlated positively with maternal weight before and at the end of gestation, without differences between groups. Cord leptin is higher in LGA and lower in SGA, whereas placental leptin is higher in SGA. Placental leptin was inversely correlated with placental weight, independently from maternal weight and gestational age. Both LEPRa and LEPRb expression are lower in SGA, while LEPRa positively correlated with placental weight and birthweight. The current findings indicate that placental leptin and its receptors are differentially expressed in SGA, AGA, and LGA newborns. We suggest that placental leptin and LEPR protein expression may influence placental growth and thus, birth weight.
Keywords: placenta; leptin receptor; leptin; birth weight